Women's Poetry of the Great War - Bureš, Jaroslav (Univerzita Pardubice, 2020)
The aim of this bachelor's thesis is to analyse typical themes reoccurring in the woman's poetry of the era of the First World War. The thesis is divided into three theoretical chapters, each accompanied by a practical subchapter. In the first chapter, the area of women's working opportunities during the First World War is described. The second chapter covers the area of religion, it consists of description of official clergy's attitude towards the conflict, contradictory movements and work of army clergymen. The final, third chapter focuses on the propagandistic tendencies, its processes and contradictory pacifist movements active during the conflict, where women played a role.
Ženská poezie v období první světové války
Keywords: Británie; poezie; ženy; velká válka; náboženství; propaganda; práce; Britain; poetry; women; Great War; religion; propaganda; labour